Blood transfusion and the presence of biological structures in the circulation: Circulating supramolecular structures and blood transfusion - Tanos, Rita; Thierry, Alain (Cellular and Molecular Biology, 2022)
Advances in knowledge continue to be made regarding biological structures which may be present in blood circulation, such as circulating cell-free DNA, extracellular vesicles, neutrophil extracellular traps (NETs), and activated platelet-derived or circulating cell-free mitochondria. These circulating elements may be of systemic significance, in particular with respect to immunomodulation and cell-to-cell communication. This fact highlights the need to take into consideration the delivery to the host of various biological structures and by-products by means of blood- or blood products transfusion; and to investigate their potential side effects. The significance of these structures and their reported potential effects are discussed in this review. However, to date, no evidence of deleterious effect following blood or blood products transfusion was reported.